The role of the Fontan operation in the treatment of congenitally corrected transposition of the great arteries - Tom R Karl (Wolters Kluwer Medknow Publications, 2011)
Congenitally corrected transposition of the great arteries (ccTGA) is a complex cardiac anomaly with an unfavorable natural history. Surgical treatment has been available for over 50 years. Initial procedures used for ccTGA did not correct atrio-ventricular discordance, leaving the right ventricle in systemic position. In the past two decades anatomic repair has been considered to be a better option. Many cases subjected to anatomic repairs would also be suitable for the Fontan strategy, which probably has a lower initial risk. The rationale for use of the Fontan operation in management of congenitally corrected transposition is discussed in this review, with comparisons to other strategies.